2010
DOI: 10.2174/156720510790691100
|View full text |Cite
|
Sign up to set email alerts
|

From Anti-allergic to Anti-Alzheimer ’ s: Molecular Pharmacology of Dimebon™

Abstract: Dimebon, originally developed as an anti-histamine drug, is being re-purposed for new indications as an effective treatment for patients suffering from Alzheimer's and Huntington's diseases, albeit with an as-yet unknown mechanism of action. We have performed molecular pharmacology profiling of this drug on a panel of 70 targets to characterize the spectrum of its activity, with the goal to possibly elucidate a potential molecular mechanism for the re-purposing of this drug candidate. We show that in addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 65 publications
1
50
0
3
Order By: Relevance
“…According to this concept, the mechanisms responsible for the beneficial actions of drugs can be realised via multiple actions of the compound on a number of receptors; in this case, effective changes in the concentrations of neurotransmitters may be much lower than if only one receptor signaling system underlies the drug's activity. On one hand, dimebon was shown to interact with a broad spectrum of neuronal receptors, which are involved in synaptic plasticity and cognitive functions Schaffhauser et al, 2009;Grigoriev, 2009;Giorgetti et al, 2010;Okun et al, 2010). At the same time, effects from dimebon on pre-clinical and clinical measures of cognition were found at doses corresponding to brain concentrations much lower than the K1 values for many receptors which were found to be effective in models of learning and memory (Gold, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to this concept, the mechanisms responsible for the beneficial actions of drugs can be realised via multiple actions of the compound on a number of receptors; in this case, effective changes in the concentrations of neurotransmitters may be much lower than if only one receptor signaling system underlies the drug's activity. On one hand, dimebon was shown to interact with a broad spectrum of neuronal receptors, which are involved in synaptic plasticity and cognitive functions Schaffhauser et al, 2009;Grigoriev, 2009;Giorgetti et al, 2010;Okun et al, 2010). At the same time, effects from dimebon on pre-clinical and clinical measures of cognition were found at doses corresponding to brain concentrations much lower than the K1 values for many receptors which were found to be effective in models of learning and memory (Gold, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another CoQ10 derivative, mitoquinone mesylate or mitoQ, has also been applied to prevent oxidative damage in AD [119] . Latrepirdine (Dimebon), a nonselective antihistamine, has shown promise in vitro for preventing ROS-mediated damage in neurodegenerative diseases [120] . In a phase-2 trial, Dimebon was found to be well-tolerated and improved cognition, activities of daily living, and overall function in MCI and AD patients as compared to placebo [121] .…”
Section: Antioxidants As a Treatment For Alzheimer's Diseasementioning
confidence: 99%
“…Despite numerous ongoing clinical trials, of date no experimental therapeutics have survived the ultimate test of a phase III clinical trial. Among the most recent failures are trials with AN1792 (active anti-Ab immunization), Dimebon (an antihistamine with additional multiple mechanisms of action, for review see Okun et al, 2010), Ginkgo biloba (an anti-oxidant), tarenflurbil (a g-secretase modulator), and semagacestat (a g-secretase inhibitor, GSI). Most of these experimental therapeutics, particularly those focused on antiamyloid strategies, have been validated in mouse models of amyloidosis.…”
Section: Major Directions Of Mechanism-based Therapeutics Developmentmentioning
confidence: 99%